What is a better modality of maxillomandibular fixation: bone-supported arch bars or Erich arch bars? A systematic review and meta-analysis. Issue 8 (October 2021) - Jain, A.; Taneja, S.; Rai, A.
Abstract: Any procedure that aims to manage maxillofacial fracture is incomplete without meticulous maxillomandibular fixation (MMF). For decades, Erich arch bars (EABs) have been used for this purpose, but with the advent of bone-supported arch bars (BSABs), more surgeons now prefer them to conventional EABs. The present study was designed to identify which of the two methods is best. An exhaustive literature search was conducted in June 2020 on various electronic databases to select studies that compared EABs and BSABs. Outcomes such as duration of placement, stability, oral hygiene, and complications such as damage to the roots of teeth and needle-stick injury, were analysed. A total of 716 studies were identified, of which seven were eligible for inclusion. The meta-analysis showed that the use of BSABs is significantly faster with no needle penetration and better oral hygiene. Both arch bars are equally stable, but root damage is an associated complication. The available literature to date shows that BSABs are a better option than EABs. However, further research is recommended, as these studies are associated with various confounding factors.